Mechanical and microstructural studies in a polysaccharide-acrylate double network hydrogel - Torris, Arun; Nair, Sanoop; Mol, K. P. Raji; Sengupta, Poulomi; Badiger, Manohar (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Polymeric hydrogels continue to find a wide range of applications. However, a major drawback of hydrogels is the lack of mechanical strength. In this regard, ``Double Network Hydrogels'' (DN) have shown great promise recently. The toughness in DN hydrogels originates from the synergistic effect of two polymeric networks. In this work, we have synthesized a DN hydrogel consisting of a tightly cross linked carboxymethylcellulose (CMC) as the first network and loosely cross linked poly(hydroxyethylacrylate) (PHEA) as a second network (CMC-PHEADN). The required flexibility in the second network (PHEA) was induced by the presence of a small amount of stearyl methacrylate (SM) as a co-monomer in hydroxyl ethyl acrylate (HEA). The compressive strength of the CMC-PEHA-DN hydrogel was found to be 280 times more than that of CMC-SN hydrogel, and the presence of SM in DN hydrogels showed better recovery after deformation. Cell viability studies showed the biocompatibility of DN hydrogels. The micro-structural analysis of DN xerogels by 3D X-ray Microtomography indicated the presence of oriented pores in size range of 30-40 mu m. To the best of our knowledge, Microtomography was used for the first time to study the DN gels. These hydrogels can be used to develop implants that can withstand prolonged stress and expand the life span of implants.
Keywords: Carboxymethyl cellulose; Double network hydrogels; Poly(hydroxyethyl acrylate); Poly(hydroxyethyl-co-stearyl methacrylate)

Microgels of hydrophobically modified-ethyl hydroxy ethyl cellulose (HM-EHEC) with 5-flurouracil for drug delivery applications - Wali, Ashwini; Badiger, Manohar (Research Journal of Biotechnology, 2025)
The polysaccharides (e.g. celluloses and proteins) which form the basic building blocks of life, are gaining increased interest in recent times for researchers to develop newer health care products from renewable bio-polymers which are cheaper and easily available with different desirable properties. Gels are highly swollen three dimensional networks of hydrophilic polymers cross-linked by physical or chemical interactions. Our focus was to design and develop a novel microgel system which would effectively deliver the anti-cancer drug to the targeted site by slow and sustained release for longer times. The water soluble hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) biopolymer was used in the synthesis of microgels by Michael-type addition reaction between the primary hydroxyl groups of HM-EHEC and Divinyl sulphone (DVS) crosslinker using water-in-oil emulsion technique. The microgels obtained were spherical in shape having flower type morphology with average size of 5 to 8 μm. The anti-cancer drug 5-Flurouracil (5-FU) drug was successfully incorporated and around 56% of the 5-FU was released in 72 hours with a loading efficiency of 95%. The cell viability (MTT assay) studies confirmed the cycto-toxicity on the MDA-MB 231 breast cancer cell line. There was an increase in the cell death with increase in the concentration of microgel containing drug concentration. The HM-EHEC microgels could be effectively used in the form of a topical cream in the skin and breast cancer for on-site slow and targeted delivery.